Description of Dental and Oral Hygiene and Extrinsic Dental Stain Among E-Cigarette Smokers in the Vaper Community in Tasikmalaya City - Rahmi Sugiharti; Yayah Sopianah; Rena Setiana Primawati; Emma Kamelia (Dental Therapist Journal, 2023)
Smoking behavior can have a negative effect on health. It not only causes a systemic effect, but can also cause pathological conditions in the oral cavity. The World Health Organization is pursuing a strategy by replacing the use of conventional cigarettes with electric cigarettes, because they do not contain tar and carbon monoxide compounds, although some evidence says that vaping or e-cigarettes have not been proven safe. This study aims to determine the description of dental and oral hygiene and extrinsic dental stain among e-cigarette smokers in the vaper community in Tasikmalaya City. This was a descriptive study which presents a complete description of the problem under study. The study samples involved 43 respondents. The study used the assessment instruments of OHIS Green and Vermillion index and the extrinsic stain index according to Shaw and Murray. 43 respondents were willing to be examined for the mouth condition. The results of the study showed that 58% of respondents had moderate dental and oral hygiene status. 61% of respondents had moderate level of extrinsic dental stain. It can be concluded that the Vaper community in Tasikmalaya City had a moderate status of oral hygiene and extrinsic dental stain. It is recommended that future researchers can observe a comparison of oral and dental hygiene between conventional smokers and e-cigarette smokers so that it is expected to increase public knowledge about the impact of cigarettes and e-cigarettes on dental hygiene and stain.